Effects of Differing Dosages of Pomegranate Juice Supplementation after Eccentric Exercise. (29th September 2014) - Machin, Daniel R.; Christmas, Kevin M.; Chou, Ting-Heng; Hill, Sarah C.; Van Pelt, Douglas W.; Trombold, Justin R.; Coyle, Edward F.
Abstract : Dietary supplementation with pomegranate juice improves isometric strength recovery after unaccustomed eccentric exercise. The purpose of this study was to determine if there is a dose response effect of pomegranate juice supplementation after eccentric exercise isometric strength recovery. Forty-five nonresistance trained, recreationally active men were assigned once-daily pomegranate juice, twice-daily pomegranate juice, or placebo supplementation. On day four of supplementation, 20 min of downhill running and 40 maximal eccentric elbow flexion repetitions were performed. Isometric knee extensor and elbow flexor strength, muscular soreness, and serum myoglobin concentrations were measured prior to exercise and 2, 24, 48, 72, and 96 h after exercise. Throughout the postexercise time period, while isometric knee extensor and elbow flexor strength were similar between once-daily and twice-daily pomegranate juice supplementation groups, isometric strength was significantly higher in pomegranate juice groups than placebo. Knee extensor soreness, elbow flexor soreness, and myoglobin increased in response to exercise but were similar between groups. It is apparent that pomegranate juice supplementation improves strength recovery in leg and arm muscles following eccentric exercise; however, no dose response effect was present. We conclude that once-daily pomegranate juice supplementation is not different from twice-daily supplementation in regards to strength recovery after eccentric exercise.